Research progress on the utilization of caproic acid bacteria for pit mud maintenance - FENG Wencong, SUN Wei, MAO Wending, LV Le, YIN Xiangxiang, CHEN Maobin, FANG Shangling (Zhongguo niangzao)
Caproic acid bacteria are functional microorganisms that produce caproic acid in pit mud, and caproic acid is the precursor of ethyl caproate, a characteristic flavor compound of strong-flavor (Nongxiangxing) Baijiu. Therefore, caproic acid bacteria are crucial in the production of strong-flavor Baijiu. In this paper, the sources of caproic acid bacteria production in pit mud, caproic acid synthetic metabolic pathways, and the relationship between pit mud quality indicators and caproic acid bacteria were briefly introduced. The application of caproic acid bacteria in new artificial pit mud and pit mud maintenance was mainly elaborated. The research aims to maintain the balance of microecology inside the pit mud, meet the needs of pit mud maintenance, and improve the quality of Baijiu.